PROMOTING LEARNER AUTONOMY IN SELF-ACCESS CENTRES: THE KEY ROLE OF MATERIAL - Navarro Coy, Marta; Brady, Imelda Katherine (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract Self-access centres (SACs) have in the abundant literature on the theme been subject to quite a number of definitions and classifications. The many types of so called SACs can all be considered valid within their particular context. However, it is the aim of this paper to study the role that materials can play in this type of learning context and, especially, in those SACs that have been created with the aim of promoting learner autonomy. With this purpose in mind we shall outline the different types of materials usually encountered in a self-access centre in an attempt to reflect their relevance within those centres that aim at helping learners in becoming fully responsible for the learning process and, in consequence, in becoming autonomous learners.